2019
DOI: 10.1016/j.cub.2019.01.072
|View full text |Cite
|
Sign up to set email alerts
|

Little Adaptive Potential in a Threatened Passerine Bird

Abstract: Highlights d The hihi has a low genetic diversity from genomic data compared to other birds d The heritability of a range of adaptive traits is inferred to be low to very low d The additive genetic variance of relative fitness is inferred to be very low d These results converge toward a strong lack of adaptive potential in the hihi Authors

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
86
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(93 citation statements)
references
References 53 publications
6
86
1
Order By: Relevance
“…; de Villemereuil et al. ), our results demonstrate the persistence of high V A (W) despite contemporary selection. Significant interactions between genotype and year reflected modest correlations between years of family‐specific breeding values for lifetime fitness, as well as estimates of V A (W) that varied widely across years.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…; de Villemereuil et al. ), our results demonstrate the persistence of high V A (W) despite contemporary selection. Significant interactions between genotype and year reflected modest correlations between years of family‐specific breeding values for lifetime fitness, as well as estimates of V A (W) that varied widely across years.…”
Section: Discussionsupporting
confidence: 70%
“…Whereas numerous authors invoke relentless selection to explain limited heritability of total fitness, or traits closely related to fitness (Kruuk et al 2000;Coltman et al 2005;McFarlane et al 2014;de Villemereuil et al 2019), our results demonstrate the persistence of high V A (W) despite contemporary selection. Significant interactions between genotype and year reflected modest correlations between years of family-specific breeding values for lifetime fitness, as well as estimates of V A (W) that varied widely across years.…”
Section: Discussioncontrasting
confidence: 55%
“…With sufficient sample sizes, individual-level relatedness may provide more sensitive detection of recent population collapse than population-level diversity, which can take multiple generations to change appreciably. The remaining genetic diversity in Raso Larks is likely to be of critical importance for their future adaptive potential [10]. This is especially relevant given the vulnerability of Cape Verde to environmental changes such as climate change [50] and the ongoing reintroduction of Raso larks to the nearby island of Santa Luzia, initiated in April 2018.…”
Section: Discussionmentioning
confidence: 99%
“…It was possible, for instance, to reveal a lack of adaptive potential in a threatened New Zealand bird species by combining quantitative genetics with long‐term phenotypic data and fitness proxies (de Villemereuil et al. ). It has further been shown that SDMs lacking quantitative genetics can vastly underestimate species range dynamics, for example, range expansions in Aedes aegypti , the mosquito that transmits dengue virus (Kearney et al.…”
Section: Prediction Models Of Species Responses To Global Climate Changementioning
confidence: 99%